The Miracle of Sciences: Between Authenticity and Constraint | الإعجاز العلمي بين التأصيل والتكلف - Sulaiman Al Shueily; Mabrouk Chibani Mansouri; Mohammed Al Garbi (Al-Zahra : Journal for Islamic and Arabic Studies, 2020)
Scientific Miracles is a type of Qur’anic Miracles that perhaps might be considered the most common one in this day and age. Scholars have different opinions regarding Scientific Miracles, while it is braced by the majority of scholars as a way to spread Islam, others oppose it fearing that it could lead to a misunderstanding to the meanings of the Qur’anic verses. This paper analyzes the views of the two parties and discusses some examples of Scientific Miracles in the Qur’an, (splitting of the moon, blotting the sign of the night, Saying the name of Allah while slaughtering). The study relies upon fudamantal resouses in the field such as the books authored by Dr. Zaghloul al Najjar along with trusted websites. The paper then concludes with several key points which includes that the splitting of the moon is not an actual physical split, but rather some sort of moon eclipse. As for blotting the sign of night, it was settled that Allah has created the night dark as it is without the bright light in contrast to the day. Lastly, saying the name of Allah while slaughtering is only a way of worshiping the almighty creator. Thus, we have to be careful not to include Scientific Miracles as Qur’anic Miracles if it cannot be proven scientifically.